Emulsion-Based Nanostructures for the Delivery of Active Ingredients in Foods - Salvia-Trujillo, Laura; Artiga-Artigas, María; Molet-Rodríguez, Anna; Turmo-Ibarz, Ana; Martín-Belloso, Olga (Frontiers in Sustainable Food Systems, 2018)
This review aims at presenting recent advancements on the design of novel emulsion-based nanostructures for an effective incorporation of active ingredients into foods. The specific characteristics of nanoemulsions, solid lipid nanoparticles, and double emulsions are highlighted. Nanoemulsions are oil-in-water emulsion with droplet sizes below 200 nm that are known to present high stability over time. Moreover, due to their reduced droplet size and therefore maximized active surface area, they are capable of enhancing the interactions with biological systems, such as foods. For instance, nanoemulsions present an improved functionality of active ingredients and a fast digestibility under gastrointestinal conditions leading to an optimal absorption of bioactive ingredients contained within them. Solid lipid nanoparticles are particularly effective for protecting lipophilic active ingredients in their lipid inner core, since the crystalline state of the lipid droplets can reduce the oxidative and degradation processes occurring in aqueous systems. Nevertheless, their formulation should be carefully selected in order to obtain the desired effect. Lastly, double emulsions are defined as emulsions of an emulsion. Therefore, their formation consists on the formation of a primary water-in-oil emulsion and its subsequent further emulsification in a secondary aqueous system. This allows the encapsulation of hydrophilic active compounds in the inner aqueous phase. Their stabilization remains as a scientific challenge yet they present promising applications. The main key aspects for the formation, stabilization and their behavior during gastrointestinal conditions are addressed.